Pharmacokinetics of Azalomycin F, a Natural Macrolide Produced by Streptomycete Strains, in Rats - Su He (MDPI AG, 2021)
As antimicrobial resistance has been increasing, new antimicrobial agents are desperately needed. Azalomycin F, a natural polyhydroxy macrolide, presents remarkable antimicrobial activities. To investigate its pharmacokinetic characteristics in rats, the concentrations of azalomycin F contained in biological samples, in vitro, were determined using a validated high-performance liquid chromatography–ultraviolet (HPLC-UV) method, and, in vivo, samples were assayed by an ultra-high performance liquid chromatography–tandem mass spectrometric (UPLC–MS/MS) method. Based on these methods, the pharmacokinetics of azalomycin F were first investigated. Its plasma concentration-time courses and pharmacokinetic parameters in rats were obtained by a non-compartment model for oral (26.4 mg/kg) and intravenous (2.2 mg/kg) administrations. The results indicate that the oral absolute bioavailability of azalomycin F is very low (2.39 ± 1.28%). From combinational analyses of these pharmacokinetic parameters, and of the results of the in-vitro absorption and metabolism experiments, we conclude that azalomycin F is absorbed relatively slowly and with difficulty by the intestinal tract, and subsequently can be rapidly distributed into the tissues and/or intracellular f of rats. Azalomycin F is stable in plasma, whole blood, and the liver, and presents plasma protein binding ratios of more than 90%. Moreover, one of the major elimination routes of azalomycin F is its excretion through bile and feces. Together, the above indicate that azalomycin F is suitable for administration by intravenous injection when used for systemic diseases, while, by oral administration, it can be used in the treatment of diseases of the gastrointestinal tract.